First record of Epipompilus excelsus (Bradley, 1944) (Hymenoptera, Pompilidae) as a koinobiont ectoparasitoid of Ariadna mollis (Holmberg, 1876) (Araneae, Segestriidae) - Villanueva-Bonilla, German Antonio; Brescovit, Antonio Dom Ingos; Santos, Eduardo Fernando dos [UNESP]; Vasconcellos-Neto, Joao (Pensoft Publ, 2018)
Epipompilus Kohl comprises 52 species of wasps that are parasitoids of spiders; 16 species occur in the Neotropical region and 36 species occur in the Australian region. The biological knowledge of this genus is limited and its interactions and host spiders are still incipient. Here, we report some behavioural and biological characteristics of E. excelsus, a parasitoid of the tube-dwelling spider Ariadna mollis. We observed an E. excelsus female attacking an adult female of A. mollis in Sao Paulo, Brazil. We photographed daily the larval development of the wasp, from the egg stage to adult emergence. The entire developmental cycle of the wasp took 24 days. This period was shorter than the developmental periods of wasps belonging to other genera of Pompilidae. Although all species within Pompilidae use spiders as host, they present great behavioural diversity, characterized by different ethological sequences. In conclusion, this study demonstrated that the Neotropical species of Epipompilus exhibit biological characteristics similar to the Australian species, acting as a koinobiont ectoparasitoid, but displays differences in larval morphology. Studies on other species could elucidate the extent of these differences and similarities, contributing to our understanding of the evolutionary history of Epipompilus, and consequently of Pompilidae.
Keywords: Egg-wasp development; Neotropical; Parasitoid; Tube-dwelling spider